Time Dependent Performance of ITER90H-P Fusion Reactor with Considering D-T and D-3He Fuel - S. N. HOSSEİNİMOTLAGH and S. KİANAFRAZ and Sakineh GHADERİ (International Journal of Applied Methods in Electronics and Computers, 2015)
In thermonuclear fusion research using magnetic confinement, the tokamak is the leading candidate for achieving conditions required for a reactor. An international experiment, ITER is proposed as the next essential and critical step on the path to demonstrating the scientific and technological feasibility of fusion energy. ITER is to produce and study plasmas dominated by self-heating. This would give unique opportunities to explore, in reactor relevant conditions, the physics of α-particle heating, plasma turbulence and turbulent transport, stability limits to the plasma pressure and exhaust of power and particles. Our studies show that in the dynamical state physical quantities are dependent on temperature and time .Each has its own specific variations and also at the temperature 70 (Kev) these quantities produce the maximum fusion gain for both of fuels D – T and,D- 3 He such that their values are equal to 81.311 for D - T fuel-and the 0.0429 for D- 3 He at one second after occurring fusion t=1s ,respectively.